GENERALIZED EXPONENTIAL OPERATORS AND DIFFERENCE EQUATIONS - Asif, Mohammad; Gupta, Anju (Italian Journal of Pure and Applied Mathematics, 2014)
The present paper deals with the generalization of exponential operators used by Dattoli and Levi for translation and diﬀusive operator which were utilized to establish analytical solutions of diﬀerence and integral equations. The generalization of their technique is expected to cover wide range of such utilization.